Synthesis of Ni-doped ZnO nanostructures by low-temperature wet chemical method and their enhanced field emission properties - Rana, Amit Kumar; Bankar, Prashant; Kumar, Yogendra; More, Mahendra A.; Late, Dattatray J.; Shirage, Parasharam M. (RSC Advances, 2016)
In this study, we report an enhancement in the field emission (FE) properties of ZnO nanostructures obtained by doping with Ni at a base pressure of similar to 1 x 10(-8) mbar, which were grown by a simple wet chemical process. The ZnO nanostructures exhibited a single-crystalline wurtzite structure up to a Ni doping level of 10%. FESEM showed a change in the morphology of the nanostructures from thick nanoneedles to nanoflakes via thin nanorods with an increase in the Ni doping level in ZnO. The turn-on field required to generate a field emission (FE) current density of 1 mu A cm(-2) was found to be 2.5, 2.3, 1.8 and 1.7 V mu mcm(-2) for ZnO (Ni0%), ZnO (Ni5%), ZnO (Ni7.5%) and ZnO (Ni10%), respectively. A maximum current density of similar to 872 mu A cm(-2) was achievable, which was generated at an applied field of 3.1 V mu m cm(-2) for a Ni doping level of 10% in ZnO. Long-term operational current stability was recorded at a preset value of 5 mA for a duration of 3 h and was found to be very high. The experimental results indicate that Ni-doped ZnO-based field emitters can open up many opportunities for their potential use as an electron source in flat panel displays, transmission electron microscopy, and the generation of X-rays. Thus, the simple low-temperature (similar to 80 degrees C) wet chemical synthesis approach and the robust nature of the ZnO nanostructure field emitter can provide prospects for the future development of cost-effective electron sources.